(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Nowadays, Item analysis is an important tool to know the functionality of the set items used in a test, prepared to access the learning level of student. An item which is a multiple-choice question with more than one option out of one is a correct answer called a key and the rest is an incorrect answer(s) called a distractor(s). The main objective of the distractor is to divert the student from the correct answer. Good distractor(s) is always a plausible answer. So to understand the function of the distractor(s), the distractor analysis is very important. In this study, we analyzed the different statistics of item analysis namely difficulty index, discrimination index, distractors, etc. and understand how they are functioning.